Representation of Social Class and Social Injustice in Mira Widjaja's Novel Di Balik Kabut Amnesia - Najla Salsabila; Zahra Alwi (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze the versification (science of 'arudh) and moral values ??in Diwan Ibn al-Adim. The focus of this study includes identifying the types of bahar and zihaf used in the composition of the verses of the poem and the disclosure of the moral values ??contained therein. This study employs a qualitative descriptive method, combining the arudh science approach to analyze the structure of the poem's meter with the Islamic moral studies approach to interpret the moral messages of literary works. The research data sources are selected verses of poetry from Diwan Ibn al-Adim obtained through the Diwanul al-‘Arabi application. The data were analyzed through the following stages: (1) classification of the verses of the poem, (2) analysis of the wazan, taf'ilah, and bahar patterns according to the theory of science of 'arudh, and (3) interpretation of the content of moral values ??contained in the text. The results of the study show that Diwan Ibn al-'Adim is dominated by the use of bahar Basith, Thawîl, and Kamil with variations of zihaf such as khaban, qabdh, and idhmar. From a moral perspective, various values are found, including tawadhu, sabar, jujur, iffah, wara', hikmah, zuhud, generosity, responsibility, and piety. In addition, this work also contains moral messages that cover human relations with Allah SWT, fellow humans, and the social environment. This study concludes that Diwan Ibn al-'Adim is a literary work that is not only aesthetically superior due to its strong poetic structure but also rich in moral education that remains relevant throughout time. These findings are expected to contribute to the development of Arabic literary studies, especially those that integrate aspects of form and value.